EARLY INITIATION OF BREASTFEEDING AS A PROTECTIVE STRATEGY AGAINST NEONATAL SEPSIS : A REVIEW OF CURRENT EVIDANCE - Siagian, Elisyah; E. Tiomarlina Sitorus Pane; Eka Kristiyanti Gea; Eka Masita Dongma Tampubolon; Siti Nurmawan Sinaga (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background:Neonatal sepsis remains one of the leading causes of neonatal morbidity and mortality worldwide. Early Initiation of Breastfeeding (EIBF), defined as breastfeeding within the first hour after birth, has been recognized as a simple, effective, and cost-efficient intervention that may reduce the risk of neonatal infections. Through the provision of colostrum and the enhancement of neonatal immune function, EIBF plays a crucial role in improving neonatal health outcomes and survival.Objective: To review current evidence regarding the role of Early Initiation of Breastfeeding (EIBF) as a protective strategy against neonatal sepsis.Methods:A literature review was conducted using articles retrieved from PubMed, Scopus, ScienceDirect, Google Scholar, and SpringerLink. The search included studies published between 2021 and 2025 using keywords related to early initiation of breastfeeding, colostrum, neonatal sepsis, and neonatal health outcomes. Eligible articles were selected based on their relevance and analyzed using a thematic approach to identify key findings regarding the relationship between EIBF and neonatal sepsis prevention.Results:The reviewed literature demonstrated that EIBF contributes significantly to reducing the risk of neonatal infections, including neonatal sepsis. This protective effect is primarily attributed to the immunological benefits of colostrum, which contains antibodies, immune cells, and bioactive components that enhance neonatal immunity. EIBF also supports the establishment of healthy intestinal microbiota and improves overall neonatal adaptation after birth. Furthermore, studies reported that EIBF is associated with lower rates of neonatal morbidity and mortality. However, several barriers to EIBF implementation were identified, including cesarean delivery, inadequate breastfeeding support from healthcare providers, and limited maternal knowledge regarding the benefits of early breastfeeding initiation.Conclusion:Early Initiation of Breastfeeding is an effective strategy for preventing neonatal sepsis and improving neonatal health outcomes. Strengthening EIBF practices through health education, supportive healthcare policies, and enhanced breastfeeding support should be prioritized as part of comprehensive neonatal healthcare programs to reduce neonatal morbidity and mortality.